Determinants Of Supply Chain Management (SCM)- Malaysian Perspective - Ramasamy, Haemala (2008)
The main objectives of this research are to identify the factors stimulate advances in supply Chain Management and to understand the impact of Supply Chain Management in Malaysian industries.